An Ethical Perspective of Nursing Care Rationing and Missed Care - Suhonen Riitta; Scott Anne P; Igoumenidis Michael (Springer, 2022)
This chapter discusses ethical issues in the area of rationing and missed nursing care from two different perspectives: (1) philosophical/conceptual and (2) empirical descriptive ethics. In addition, ethical issues can be approached from (1) the societal and organisational levels, i.e. organisational ethics, (2) the professional nursing staff, i.e. professional ethics and (3) the service user’s and patient’s point of views, from the perspective of rights. These approaches may look at different sides of the same issue, and deserves closer investigation and discussion. The use of the concepts missed care, care left undone, unfinished care and covert rationing of care varies in the literature, potentially giving rise to some conceptual confusion, inconsistencies and potential misunderstandings. This can lead to unidentified, flawed assumptions and difficulties in clarity of thought regarding the phenomenon/phenomena under question. Finally, the empirical evidence on the missed care/ rationing and similar concepts deserves some conclusive statements from the ethics point of view.
Impacts of Rationing and Missed Nursing Care: Challenges and Solutions – RANCARE Action